Mechanical properties and uniformity of Fe-MgB2 wires upon various wire drawing steps - Karaboğa, Fırat; Ülgen, Asaf Tolga; Yetiş, Hakan; Akdoğan, Mustafa; Pakdil, Murat; Belkenli, İbrahim (MATERIALS SCIENCE AND ENGINEERING A-STRUCTURAL MATERIALS PROPERTIES MICROSTRUCTURE AND PROCESSING, 2018)
Effect of drawing process on the mechanical properties and cross-sectional uniformity of Fe/MgB2 mono-filamentary wires were investigated in this study. Successive cold drawing steps were applied with and without intermediate strain relief annealing steps. Micro-hardness measurements of the drawn wires were taken from the polished cross-sections. Tensile tests were performed on the 120 mm long wires samples. Microstructural properties of the sheathing material and that of the superconducting core were studied using SEM. Uniformity of the cross-sectional area in final mono filamentary wires was studied on SEM images of the polished cross sections. Excessive mechanical deformation of the soft iron sheathing metal via drawing was assessed and discussed.
Keywords: Superconducting Wires; Magnesium Diboride; Micro-hardness and Mechanical Properties